De novo variants in RAB11B cause various degrees of lobal developmental delay and intellectual disability in children - Ahmad, Natalie; Fazeli, Walid; Schließke, Sophia; Lesca, Gaetan; Gokce-Samar, Zeynep; Mekbib, Kedous Y.; Jin, Sheng Chih; Burton, Jennifer; Hoganson, George; Petersen, Andrea; Gracie, Sara; Granger, Leslie; et al. (Pediatric neurology, 2023)
Background - RAB11B was described previously once with a severe form of intellectual disability. We aim at validation and delineation of the role of RAB11B in neurodevelopmental disorders. - Methods - We present seven novel individuals with disease-associated variants in RAB11B when compared with the six cases described in the literature. We performed a cross-sectional analysis to identify the clinical spectrum and the core phenotype. Additionally, structural effects of the variants were assessed by molecular modeling. - Results - Seven distinct de novo missense variants were identified, three of them recurrent (p.(Gly21Arg), p.(Val22Met), and p.(Ala68Thr)). Molecular modeling suggests that those variants either affect the nucleotide binding (at amino acid positions 21, 22, 33, 68) or the interaction with effector molecules (at positions 72 and 75). Our data confirmed the main manifestations as neurodevelopmental disorder with intellectual disability (85%), muscular hypotonia (83%), structural brain anomalies (77%), and visual impairment (70%). Combined analysis indicates a genotype-phenotype correlation; variants impacting the nucleotide binding cause a severe phenotype with intellectual disability, and variants outside the binding pocket lead to a milder phenotype with epilepsy. - Conclusions - We confirm that disease-associated missense variants in RAB11B cause a neurodevelopmental disorder and suggest a genotype-phenotype correlation based on the impact on nucleotide binding functionality of RAB11B.